Resource Estimation of the Goaf Area in Shoushan Mine - Su, Yanli (International Journal of Natural Resources and Environmental Studies, 2025)
Starting with the exploration data of coalbed methane (CBM) in the Shoushan block, this study analyzes the distribution of the main coal seam and the layout of the mined-out wells in the coal-bearing strata of this area. The main coal seam in this block belongs to the Permian system. It is characterized by considerable thickness and high gas content. According to the relevant industry standards for calculating CBM volume, and based on the data from drilled wells, the estimated CBM resources are approximately 2.5×10⁸ m³, with a resource abundance of 0.46×10⁸ m³/km², indicating favorable prospects for CBM development in this block.